CIREBON BATIK E-BOOK DESIGN WITH POP ART ILLUSTRATION STYLE: Case Study Katura Studio At Trusmi Cirebon (Universitas Tunas Pembangunan Surakarta, 2023)
Batik culture has emerged in Cirebon since the monarchy era’s and has many types of batik motifs. People, especially the younger generation, don't know about Cirebon batik and its types other than Mega Mendung batik. This is due to a lack of publication and provision of information. Based on this background, we designed a guidebook, especially in the form of a digital book (e-book). This research uses a qualitative research method focusing on digital book design, using the participant's point of view as the preferred image in obtaining research results. The data collection techniques used were observation, interviews and questionnaires, literature studies, references, documentation and supporting theories in this design. The author designed a guidebook in digital form (e-book) with Cirebon monarchy batik motifs, pop art illustration style. Digital book media (e-books) have the advantage of being more concise and can be accessed for free in the current digital era. This e-book is also a means of preserving and providing information about Cirebon batik, so that Cirebon batik motifs, especially Cirebon monarchy batik motifs, can be known to the wider community. In this way, people will know, love and participate in preserving the local culture of the Indonesian nation.